Analisis Faktor Penyebab Keterlambatan Pengembalian Rekam Medis Rawat Inap di Rumah Sakit Baladhika Husada Jember - Insani Dzakirah; Demiawan Rachmatta Putro Mudiono; Maya Weka Santi; Erna Selviyanti (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The standard for returning outpatient medical records was 1 hour after providing polyclinic services and 1 x 24 hours after the patient was discharged. Delay in returning outpatient medical records occurs if it exceeds the predetermined standard limit. The implementation of medical records at Baladhika Husada Jember Hospital still has delays in returning inpatient medical records. Therefore, it impacts patient waiting time to get services and the accumulation of files due to the procurement of new medical record documents for visiting patients because the previous medical records were not in the filing room. This research aimed to analyze the factors causing delays in returning inpatient medical records. This type of research uses qualitative research, the subject is 1 head of a medical record unit, 1 medical record officer, 3 nurses, and 2 heads of inpatient rooms. The object of this research is inpatient medical records. The results found in this study are that the first priority has not been socialization related to SOP (Standard Operational Procedure) regarding the return of inpatient medical records so it is determined that efforts to hold routine SOP socialization, providing SOP are posted in each inpatient room by involving all nurses and record officers related to the activity of returning medical records.